Uma análise preliminar do programa Fome Zero como uma política social de desenvolvimento - Souza, Luciana Rosa de (2006)
This dissertation looked forward to apprehend social influences, economic politics and that the Program "Hunger Zero" after reached in the country the 2002 elections. The central hypothesis is that the Program "Hunger Zero" had modified during first the two years of Lula´s government. The main goal that guided it was the search for apprehending the implementation of the program "Hunger Zero" in the first years of Lula´s government, with intention to evaluate if the implementation of the social program it was related to the proposal initial presented by the government. For this the method was used theoretician-description through the reading criticizes of documents of the government and texts written on thematic the boarded one. Through the study we could accept the principal hypothesis of that the program "Hunger Zero" had its nature modified in relation to the proposal initial.